Social Work and the Making of Social Policy - Leitner, Sigrid; Leiber, Simone; Klammer, Ute (Book collections on Project MUSE., 2019)
Bringing together international case studies, this book offers theoretical and empirical insights into the interaction between social work and social policy.Moving beyond existing studies on policy practice, the book employs the policy cycle as a core analytical frame and focuses on the influence of social work(ers) in the problem definition, agenda setting, policy formulation and implementation of social policy. Twenty-three contributors offer examples of policy making from seven different countries and demonstrate how social work practitioners can become political actors, while also encouraging policy makers to become aware of the potential of social work for the social policy-making process.